Myb Immunohistochemical Staining and Fluorescence in situ Hybridization in Salivary Rare Basaloid Lesions - Li, Binbin; Jie, Weiping; He, Huiying (Frontiers in Oncology, 2020)
Objective Salivary rare basoloid lesions, including cribriform type basal cell adenoma (cBCA), BCA with incomplete capsule (iBCA), sialoblastoma (SB), and intercalated duct hyperplasia (IDH), could easily be misdiagnosed as adenoid cystic carcinoma (AdCC). We aim to identify an approach for differential diagnosis and to establish an optimal workflow concerning the diagnosis of these lesions. Material and methods A panel of antibodies (MYB, β-catenin, CD117, SOX10, ki67, P63, calponin) and fluorescence in situ hybridization (FISH)-MYB were utilized to distinguish above salivary basaloid diseases from AdCC. Results Histologically, the striking diagnostic features of cBCA, iBCA, SB and IDH composed of the basaloid tumor cells, well-defined encapsulation, or lack of the destructive invasion. Immunohistochemically, Myb immune-labeling could effectively make a distinction among cBCA, iBCA, SB and IDH from AdCC except SB. cBCA and iBCA typically expressed β-catenin in the nuclei of tumor cells. There was no statistical significance in the ki67 index between SB and AdCC, but their indices were significantly higher than those of iBCA and IDH (p<0.05, p<0.05, respectively). P63 and calponin immune-expression were observed in the basaloid or myoepithelial cells. CD117 were observed positively in cBCA, iBCA, SB and AdCC except IDH. SOX10 were observed positively in all the cases. All the cases had no fusion of MYB and NFIB detectable by FISH except in AdCC. Conclusion Considering the sensitivity and specificity, FISH-Myb and an immunohistochemical panel of MYB/β-catenin/ki67 would be an optimal choice for the differential diagnosis of these basaloid lesions.